Desenvolvimento de um software em Python para estimativa da capacidade de carga de fundações por estacas - Ferreira, Danielly Santos (2025)
The estimation of the bearing capacity of pile foundations concerns the maximum load that, theoretically, the pile-soil system can support. Such prediction is fundamental in foundation design. With software development, it is possible to automate processes such as the estimate mentioned above, which provides greater efficiency and speed in obtaining results. Once properly implemented, these software programs reduce susceptibility to human error, thus ensuring greater reliability in calculation operations. In this context, this work aimed to develop a computational code in Python based on the semi-empirical methods Aoki & Velloso (1975) and Décourt & Quaresma (1978), both adapted, to estimate the bearing capacity of foundations with bored, precast and continuous flight auger piles. The work was developed in two stages: i) implementation of the computational code based on 3 cases from the literature and preliminary analysis of the results obtained and ii) validation of the software based on 12 other cases available in the literature on the subject. The results showed that the developed software was able to provide bearing capacity for pile foundations very similar to the values in the literature, for the cases analyzed.